2020
DOI: 10.1080/01490400.2020.1774013
|View full text |Cite
|
Sign up to set email alerts
|

“Washing Hands, Reaching Out” – Popular Music, Digital Leisure and Touch during the COVID-19 Pandemic

Abstract: Through the lens of contagion theory, this paper examines the act of sanitizing tactile references in popular music at a time of legislated and extreme isolation. "Sweet Caroline" is an infectious tune that embraces togetherness and intimacy both lyrically and through its live performance. However, on March 22, 2020, Neil Diamond posted on Twitter a clip of himself, alone in front of a fireplace, singing a modified version of his hit song which reworked the lyrics of "touching hands" to "washing hands" and "to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 9 publications
0
11
0
2
Order By: Relevance
“…As I have discussed in relation to distanced performances, the fndings of this work can provide implications for the role of computer technologies in performing arts. In particular, as computermediated performing arts are becoming popular during COVID-19 [7,27], the challenge of how to convey the aura of the performances would become evident in the same manner as I observed in idol culture. For example, we need to answer a question: What motivates users to watch the paid live-streaming of a classical music concert when they have the option to play an already purchased concert recording on the same screen?…”
Section: Implications For Situations Outside Idol Culturementioning
confidence: 79%
“…As I have discussed in relation to distanced performances, the fndings of this work can provide implications for the role of computer technologies in performing arts. In particular, as computermediated performing arts are becoming popular during COVID-19 [7,27], the challenge of how to convey the aura of the performances would become evident in the same manner as I observed in idol culture. For example, we need to answer a question: What motivates users to watch the paid live-streaming of a classical music concert when they have the option to play an already purchased concert recording on the same screen?…”
Section: Implications For Situations Outside Idol Culturementioning
confidence: 79%
“…Initial studies conducted during the pandemic are positive on this score, and not just due to viral COVID-19 songs (Lehman, 2020 ). While in lockdown, Spanish people spent more time devoted to musical activities to cope, and found that music listening helped them relax, escape, raise their mood, and keep them company (Cabedo-Mas et al, 2021 ).…”
Section: Introductionmentioning
confidence: 98%
“…During the COVID-19 pandemic, many children have felt increased isolation and loneliness (Loades et al, 2020). Music has been used as a tool for encouraging health related behaviours (Lehman, 2020), for decreasing isolation and improving connectedness, and teaching and learning in music education holds promise for recovery and resilience as we move forwards (Cabedo-Mas, Arriaga-Sanz, & Moliner-Miravet, 2020;Chiu, 2020;Daubney & Fautley, 2020;Gatera & Pavarini, 2020). Though further work is required in terms of establishing more robust questionnaires for research purposes, we present this pilot study not only as a way to improve children's musicality, but also as an example of how innova-tive techniques can be used to create engaging music-based activities that can encourage children to explore their emotions in general, and generate a sense of belonging; a potentially useful application of arts-in-health for teachers and practitioners as we emerge from these difficult times.…”
Section: Discussionmentioning
confidence: 99%